Organizational and social justice paradoxes in EDI - Bosch, Anita (Frontiers in Psychology, 2024)
This perspective article positions social justice as an addition to the aims of organizational justice, and core to diversity, equality, and inclusion (DEI). It problematizes simplistic DEI rhetoric and positions paradoxes within DEI, as experienced by employers, based on an explanation of key justice concepts and the introduction of fairness, equality, desert, and need. The paper broadens perspective-taking beyond a sole focus on beneficiaries of DEI, towards tensions that employers experience in working towards the aims of workplace justice, including the embeddedness of social justice within both organizations and social systems. The paper concludes with avenues for future research and a call to carefully examine simplistic notions of organizational justice in effecting DEI, suggesting a paradoxical lens on embracing, rather than avoiding, multiple and often conflicting workplace justice imperatives.